Prevalence and clinical correlates of co-morbid attention deficit hyperactivity disorder in euthymic adults with bipolar disorder: A cross-sectional study - Vikash C. Mishra; Gunjan Solanki; Dharmdeep Singh; Manish K. Goyal (Indian Journal of Psychiatry)
Background: Bipolar disorders (BDs) are co-morbid with attention deficit hyperactivity disorder (ADHD), making diagnosis and management more difficult and associated with poorer outcomes. So, this study was planned to find the prevalence and clinical implication of co-morbid ADHD in BD. Materials and Methods: In this cross-sectional study, a total of 110 euthymic BD patients were taken. They were screened for childhood ADHD symptoms and adult ADHD symptoms using the Wender Utah Rating Scale for ADHD and Adult ADHD Self-Report Screening Scale for DSM-5. Those were divided into three groups: Group A included BD patients without ADHD, Group B included bipolar patients with co-morbid adult ADHD (BD-aADHD), and Group C included bipolar patients who had a diagnosis of childhood ADHD (BD-cADHD). Results: The ADHD prevalence of 27% was found in bipolar patients. The age of onset of an episode of BD was significantly earlier and the total duration of illness was significantly higher in BD-aADHD and BD-cADHD compared to the BD without ADHD. The BD-aADHD and BD-cADHD groups showed a significantly higher number of total, manic and major depressive episodes as compared to the BD without ADHD group. BD-aADHD showed a significant greater number of hypomanic episodes as compared to BD without ADHD. Conclusions: The present study concludes that ADHD is a lifetime co-morbid condition in adults with BD. These patients have a more chronic and disabling course of BD which underscores the need to understand the potential benefit of controlling ADHD symptoms in this population.